DESAIN DAN IMPLEMENTASI FRAMEWORK MODULAR DALAM PENGEMBANGAN SISTEM INFORMASI PENGGAJIAN PADA PT. JEKAEL INVESCO - Gulo, Fazokhi; Batubara, Supina; Erika, Winda (Smart Education, 2025)
Abstract: Developing an efficient and flexible information system is a challenge in meeting the needs of an ever-growing organization. This study aims to design and implement a modular framework in developing a payroll information system at PT. Jekael Invesco. The modular framework was chosen to provide ease in managing, developing, and maintaining the system, as well as ensuring scalability and integration with other systems. The research methods used include needs analysis, module-based system design, framework implementation, and system testing. The modular framework is designed by dividing the main functions of the system, such as employee data management, salary calculation, benefits management, and financial reporting, into independent modules that can operate in an integrated manner. The system development process follows the Agile approach to ensure that the system can be developed iteratively and adaptively according to changing organizational needs. The results of the study show that the application of a modular framework to the payroll information system provides a number of benefits, such as increased efficiency of data management, ease of adding or changing features, and reducing time and costs in the system maintenance process. In addition, this system was successfully integrated with the existing financial system at PT. Jekael Invesco, thus supporting the automation of the overall payroll process. The conclusion of this study is that the modular framework has proven effective in increasing the flexibility, efficiency, and scalability of the payroll information system. The implementation of this framework is expected to be a solution for other companies facing similar challenges in developing information systems. Keyword: Modular Framework, Payroll Information System, Agile, PT. Jekael Invesco, Systems Development Abstrak: Pengembangan sistem informasi yang efisien dan fleksibel merupakan tantangan dalam memenuhi kebutuhan organisasi yang terus berkembang. Penelitian ini bertujuan untuk merancang dan mengimplementasikan framework modular dalam pengembangan sistem informasi penggajian pada PT. Jekael Invesco. Framework modular dipilih untuk memberikan kemudahan dalam pengelolaan, pengembangan, dan pemeliharaan sistem, serta memastikan skalabilitas dan integrasi dengan sistem lain. Metode penelitian yang digunakan meliputi analisis kebutuhan, desain sistem berbasis modul, implementasi framework, dan pengujian sistem. Framework modular dirancang dengan membagi fungsi utama sistem, seperti pengelolaan data karyawan, perhitungan gaji, manajemen tunjangan, dan laporan keuangan, ke dalam modul-modul independen yang dapat beroperasi secara terintegrasi. Proses pengembangan sistem mengikuti pendekatan Agile untuk memastikan sistem dapat dikembangkan secara iteratif dan adaptif sesuai dengan perubahan kebutuhan organisasi. Hasil penelitian menunjukkan bahwa penerapan framework modular pada sistem informasi penggajian memberikan sejumlah manfaat, seperti peningkatan efisiensi pengelolaan data, kemudahan dalam penambahan atau pengubahan fitur, serta pengurangan waktu dan biaya dalam proses pemeliharaan sistem. Selain itu, sistem ini berhasil diintegrasikan dengan sistem keuangan yang ada di PT. Jekael Invesco, sehingga mendukung otomatisasi proses penggajian secara keseluruhan. Kesimpulan dari penelitian ini adalah framework modular terbukti efektif dalam meningkatkan fleksibilitas, efisiensi, dan skalabilitas sistem informasi penggajian. Implementasi framework ini diharapkan dapat menjadi solusi bagi perusahaan lain yang menghadapi tantangan serupa dalam pengembangan sistem informasi. Kata kunci: Framework Modular, Sistem Informasi Penggajian, Agile, PT. Jekael Invesco, Pengembangan Sistem